Pengaruh penggunaan learning management system dan motivasi berprestasi terhadap hasil belajar siswa program international baccalaureate di Sekolah Pelita Harapan Lippo Cikarang - Mandagie, Selanova Citra; Sumual, Shelty D. M.; Rotty, Viktory N. J. (Academy of Education Journal, 2024)
This study aimed 1) to determine the effect of using Learning Management System (LMS) on student learning outcomes, 2) to determine the effect of achievement motivation on student learning outcomes, 3) to determine the effect of using LMS and achievement motivation simultaneously on student learning outcomes in the International Baccalaureate (IB) program at Sekolah Pelita Harapan Lippo Cikarang. The research method used is quantitative research method. The research sample amounted to 32 people who were the entire population of students in the IB program (saturation sampling). The results showed that 1) The use of LMS (X1) has a positive and significant effect on student learning outcomes (Y) at Sekolah Pelita Harapan (SPH) Lippo Cikarang. This is evidenced by the results of statistical tests where the use of LMS has a significance value of 0.000 <0.05 and the value of t count> t table (4.771> 2.045); 2) Achievement motivation (X2) does not have a positive and significant effect on student learning outcomes at Sekolah Pelita Harapan Lippo. Statistical tests show that the achievement motivation variable has a significance value of 0.309> 0.05 and the t value < t table (-1.037> 2.045); 3) The use of LMS (X1) and Achievement motivation (X2) simultaneously has a positive and significant effect on student learning outcomes (Y) at Sekolah Pelita Harapan Lippo Cikarang. This is evidenced by the statistical test results where the value of Sig. 0.000 <0.05 and the calculated F value is 12.687> 3.32. The test results of the Coefficient of Determination resulted in 0.467 or 46.7%. This means that the variables of LMS usage (X1) and Achievement motivation (X2) have an influence of 46.7% on student learning outcomes (Y), the remaining 53.3% is influenced by other factors.